Iowa Birdline update, February 5, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for February 5, 1990. Highlights of the update include the large numbers of Northern Shrikes being reported in the state and the continued presence of an Evening Grosbeak. Also of note were sightings of a Red-shouldered Hawk, Merlins, 8 White-winged Crossbills and 250 Red-winged Blackbirds. Epson - sheet feed/flatbed